Models of human mobility in central-southern Patagonia through the analysis of lithic artifacts and Geographic Information Systems - Gilio, Brenda Ludmila (2022)
For a long time, Pampa del Asador was considered the main source of black obsidian in central south Patagonia, Argentina. A new secondary source with the same geochemical composition was recently found more than 170 km to the southeast, in 17 de Marzo. This paper evaluates whether the hunter-gatherers who used the basaltic canyons north of the Santa Cruz River could have utilized this latter source, given its proximity and closeness to the Deseado Massif, a source of siliceous rocks of excellent quality. The frequency, percentage, artefactual classes, medium and maximum sizes of black obsidian artifacts recovered in El Lechuza and Yaten Guajen Canyons were analyzed. This information was complemented with the frequency and percentage of artifacts made of siliceous rocks macroscopically similar to those of the Deseado Massif. The data obtained was integrated with human circulation models using Geographic Information Systems. The results suggest a greater probability for the frequency of use of the 17 de Marzo source in the case of Yaten Guajen Canyon and reinforce the possibility of the use of Pampa del Asador in the case of El Lechuza Canyon.